2011
DOI: 10.1007/s10584-011-0083-z
|View full text |Cite
|
Sign up to set email alerts
|

Sinking ships: conservation options for endemic taxa threatened by sea level rise

Abstract: Low-elevation islands face threats from sea level rise (SLR) and increased storm intensity. Evidence of endangered species' population declines and shifts in vegetation communities are already underway in the Florida Keys. SLR predictions indicate large areas of these habitats may be eliminated in the next century. Using the Florida Keys as a model system, we present a process for evaluating conservation options for rare and endemic taxa. Considering species characteristics and habitat, we assess central issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 67 publications
2
49
0
Order By: Relevance
“…In legumes, the ability to retain their symbiosis with rhizobia in increasingly saline soils is important for their persistence in the face of sea level rise, shrinking fresh water lenses, and storm surge from hurricanes. However, my results show no difference in rhizobial associates between BPK and the three mainland pine rockland soils, which suggests that if legumes from the Keys were to be moved to high grounds on the Florida mainland or elsewhere to protect them from habitat loss and other low lying areas (Maschinski et al, 2011), such translocations will move legumes to soils where suitable rhizobia are already likely to be present. This finding is also useful for potential restoration plantings.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In legumes, the ability to retain their symbiosis with rhizobia in increasingly saline soils is important for their persistence in the face of sea level rise, shrinking fresh water lenses, and storm surge from hurricanes. However, my results show no difference in rhizobial associates between BPK and the three mainland pine rockland soils, which suggests that if legumes from the Keys were to be moved to high grounds on the Florida mainland or elsewhere to protect them from habitat loss and other low lying areas (Maschinski et al, 2011), such translocations will move legumes to soils where suitable rhizobia are already likely to be present. This finding is also useful for potential restoration plantings.…”
Section: Discussionmentioning
confidence: 60%
“…Pine Key Ringneck Snake, Big Cypress Fox Squirrel, Key Deer, and the Key Mud Turtle, are amongst the species needing immediate conservation efforts (Snyder, 1990;Maschinski et al, 2011).…”
Section: Introduction I-a Pine Rocklandsmentioning
confidence: 99%
“…These forests harbor a large number of endemic populations from the Caribbean region. These populations represent the northernmost distribution of most of these plant species, all of which are threatened by environmental change (Maschinski et al 2011;Ross et al 2009;USFWS 1999). Tropical hardwood hammocks are threatened currently and historically by urbanization, anthropogenically-induced change in fire frequency, conversion to agriculture, and climate change (Harveson et al 2007;Ross et al 2001;Ross et al 2009;USFWS 1999).…”
Section: Study Species: Pilosocereus Robiniimentioning
confidence: 99%
“…Tropical hardwood hammocks are threatened currently and historically by urbanization, anthropogenically-induced change in fire frequency, conversion to agriculture, and climate change (Harveson et al 2007;Ross et al 2001;Ross et al 2009;USFWS 1999). Rising sea level is of particular concern and, coupled with a recent increase in storm frequency and intensity, is predicted to have a potentially devastating impact on the small remaining populations in the Florida Keys (Maschinski & Haskins 2012;Maschinski et al 2011). Recent habitat surveys and experiments conducted by Fairchild Tropical Botanic Garden have suggested that increasing soil salinity has contributed to the Key Tree cactus' decline and that rapid climate change is the major driving cause (Goodman et al 2012;Maschinski et al 2011).…”
Section: Study Species: Pilosocereus Robiniimentioning
confidence: 99%
See 1 more Smart Citation